Environmental indicators for assessing the state of the rural territorial community in the context of sustainable development - Pustova, Svitlana; Bogoliubov, Volodymyr (Видавництво Львівської політехніки, 2022)
The article discusses the essence and concept of sustainable development, the results of the agro-ecological assessment of the given territorial community lands, and determines the indicators of the goals of sustainable development that can be used in the local territories. The author has worked on scientific materials in Ukrainian and international professional publications and outlined the prospects for further scientific research in this direction. The general scientific, ecological, sociological, and mathematical research methods are used in the work. A brief analysis of indicator systems for forecasting the state of the environment is provided using the example of the settlement of Velyka Snitynka. It was established that the excess content of heavy metals in the soil is mainly related to the incorrect use of mineral fertilizers. It has been investigated that the assessment of the ecological state of water bodies in rural areas is an important indicator for the development of a strategy for sustainable development: the main contribution to water pollution is made by anthropogenic sources, in particular, the livestock complex and domestic manure storages and dumps. It was determined that the air quality index is a relevant indicator: exceeding the average daily concentration of fine dust indicates the need to develop programs for local monitoring of the atmospheric air.
Keywords: sustainable development goals; indicators; rural areas; concept; agro-ecological assessment